REGIONAL SCALE ASSESSMENT OF THE GROSS HYDROKINETIC ENERGY POTENTIALS OF SOME RIVERS IN LOWER NIGER RIVER BASIN, NIGERIA (Nigerian Journal of Technology, 2015)
This study investigates the hydrokinetic energy potential of some selected rivers in the Lower Niger River Basin in North Central Nigeria. The methodology adopted was to obtain the gross naturally occurring theoretical hydrokinetic potential of the rivers through the use of a hydrological model and a spatial tool. MWSWAT, an open source interface to SWAT using the GIS system MapWindow, was employed for simulation to determine the hydrological parameters of the sub-basins and other computations were done using a spreadsheet package to estimate the instantaneous power density along the river reach. Preliminary results show there are naturally occurring potentials of this technology in the Lower Niger River Basin. The estimate of the theoretical resource for the watershed totals 826.7MW (7.247TWh/yr). River Moshi has the highest discharge (8315.78 m3/secs), while Oshin has the lowest (1224.27 m3/secs). Also, Awun has the highest theoretical hydrokinetic potential of 257.5MW while Oshin has the lowest (20.9MW).   http://dx.doi.org/10.4314/njt.v34i2.29